2013
DOI: 10.4028/www.scientific.net/amm.465-466.962
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Yarn Linear Density on Mechanical Properties of Plain Woven Kenaf Reinforced Unsaturated Polyester Composite

Abstract: To produce a good quality of dry fabric for reinforced material in a natural-based polymer composite, yarn linear density should be in consideration. A woven kenaf dry fabric with three different linear densities of 276tex, 413.4tex and 759tex were produced. The fabrics with different linear densities were been optimize with the assistance of WiseTex software. The optimized dry fabrics were infused with unsaturated polyester to produce composite panel using vacuum infusion process. The composites properties we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…On the other hand, the positive correlation observed between yarn linear density and weight in this current study is in agreement with what Saiman et al (2014) found. They explained that higher linear densities result due to higher fibre loading in the yarns; in effect influencing weight and strength of the fabrics.…”
Section: Patience Asieduah Danquahsupporting
confidence: 93%
“…On the other hand, the positive correlation observed between yarn linear density and weight in this current study is in agreement with what Saiman et al (2014) found. They explained that higher linear densities result due to higher fibre loading in the yarns; in effect influencing weight and strength of the fabrics.…”
Section: Patience Asieduah Danquahsupporting
confidence: 93%
“…Numerous researches have been done by utilising natural fibre in a form of fabric to produce woven composite (Table 1). Saiman et al [21] have fabricated a series of woven kenaf composite with different yarn linear densities and weave structures using a polyester (PE) matrix through a vacuum infusion technique and have found that both parameters have a significant influence on the tensile properties of the composite. Research that has been done by Azrin Hani et al [12] have demonstrated that woven kenaf and coir have a high potential to be used as reinforcing materials, and they also concluded that fibre type and reinforcement structure parameters affect the mechanical properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to study yarn structure essentially yarn types, linear density, sizes, mechanical properties and twist effect as they determine the structure of woven fabric. Many researchers have reported results incorporating yarn properties into composite properties (Chattopadhyay 2008;Gabrijelcic et al 2008;Hani et al 2013;Junior et al 2004;Liu & Hughes 2008;Saiman et al 2014). It has been concluded that several yarn factors affect the woven fabric characteristics for composite application and it is important to pay particular attention in the selection of appropriate yarn types.…”
Section: Introductionmentioning
confidence: 99%